2010
DOI: 10.1177/104063871002200631
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal Pulmonary Choristoma in a Newborn Calf

Abstract: Abstract. A newborn male Romagnola calf, who had died a few hours after birth, was submitted for postmortem examination. Necropsy revealed a 23 cm 3 22 cm 3 5 cm, pale pink, lobulated, elastic, partially fluctuant mass that protruded from the dorsal retroperitoneal space into the abdominal cavity, extending from the diaphragm to the left kidney. The mass consisted of mature pulmonary tissue and was consistent with a pulmonary choristoma. The gross and microscopic appearance of this rare tumor-like congenital l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 14 publications
0
15
0
3
Order By: Relevance
“…Diğer evcil hayvanlarda olduğu gibi buzağılarda da farklı ürogenital sistem anomalilerine rastlanabileceği belirtilirken [5][6][7][8] böbreğin renal fossa dışında bulunması olarak tanım-lanan ektopik böbrek anomalilerine dair fazla bilgiye rastlanmamaktadır. Böbrek ektopilerinde bir veya her iki böbreğin çoğunlukla pelvis veya inguinal bölge başta olmak üzere karın ve göğüs boşluğunun herhangi bir bölümünde serbest ya da diğer organlara yapışık olarak bulunabileceği 1,3,5,6 ve üreter obstrüksiyonu ya da atrezisi olmadıkça çoğunlukla herhangi bir klinik belirti vermediği bildirilmiştir 4 .…”
Section: Tartişma Ve Sonuçunclassified
See 1 more Smart Citation
“…Diğer evcil hayvanlarda olduğu gibi buzağılarda da farklı ürogenital sistem anomalilerine rastlanabileceği belirtilirken [5][6][7][8] böbreğin renal fossa dışında bulunması olarak tanım-lanan ektopik böbrek anomalilerine dair fazla bilgiye rastlanmamaktadır. Böbrek ektopilerinde bir veya her iki böbreğin çoğunlukla pelvis veya inguinal bölge başta olmak üzere karın ve göğüs boşluğunun herhangi bir bölümünde serbest ya da diğer organlara yapışık olarak bulunabileceği 1,3,5,6 ve üreter obstrüksiyonu ya da atrezisi olmadıkça çoğunlukla herhangi bir klinik belirti vermediği bildirilmiştir 4 .…”
Section: Tartişma Ve Sonuçunclassified
“…Böbrek ektopilerinde bir veya her iki böbreğin çoğunlukla pelvis veya inguinal bölge başta olmak üzere karın ve göğüs boşluğunun herhangi bir bölümünde serbest ya da diğer organlara yapışık olarak bulunabileceği 1,3,5,6 ve üreter obstrüksiyonu ya da atrezisi olmadıkça çoğunlukla herhangi bir klinik belirti vermediği bildirilmiştir 4 . Tanı radyografi, ultrasonografi ve İVP ile konabilir 4 .…”
Section: Tartişma Ve Sonuçunclassified
“…Oliveira et al (2009) described a pulmonary choristoma associated with a meningocele in a bovine; however, the animal did not present any neurological signs and the mass was located at the subcutaneous tissue of the frontal region of the skull, preventing cranial symphysis closure. Prevalence studies providing evidence of which age range is the most frequently affected were not found; however, according to Bassi et al (2010), Brudenall et al (2008) and Oliveira et al (2009), choristomas have a higher occurrence in young cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Case descriptions of choristoma in domestic animals are uncommon to rare (WHITTEN et al, 2006), with reports in cattle (BASSI et al, 2010;BINANTI et al, 2012;BRUDENALL et al, 2008;OLIVEIRA et al, 2009), canines (BENTLEY et al, 2006WHITTEN et al, 2006) and felines (FRANÇA et al, 2010). In cattle, there are descriptions of different tissues proliferating within the thoracic cavity, diaphragm, retroperitoneal region, adrenal gland region, and subcutaneous tissue (BASSI et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation